Hospital mortality from covid-19 in children and adolescents in Brazil in 2020-2021 - Amanda Cilene Cruz Aguiar Castilho da Silva; Ronir Raggio Luiz; José Rodrigo de Moraes; Pedro Henrique Vieira Rocha; Regina Célia Gollner Zeitoune; Arnaldo Prata Barbosa; Jessica Pronestino de Lima Moreira (Universidade de São Paulo, 2023)
ABSTRACT OBJECTIVE To describe cases, deaths, and hospital mortality from covid-19 in children and adolescents in Brazil, according to age group, during the evolving phases of the pandemic in 2020 and 2021. METHODS Census of patients aged up to 19 committed with severe acute respiratory syndrome, due to covid-19 or unspecified, notified to the Brazilian Influenza Epidemiological Surveillance Information System, from January 1, 2020, to December 31, 2021. The two years were divided into six phases, covering the spread of the disease-first, second and third wave-as well as the impact of vaccination. The pediatric population was categorized into infants, preschoolers, schoolchildren, and adolescents. Hospital mortality was assessed by pandemic phase and age group. RESULTS A total of 144,041 patients were recorded in the two years, 18.2% of whom had confirmed cases of covid-19. Children under 5 years old (infants and preschoolers) accounted for 62.8% of those hospitalized. A total of 4,471 patients died, representing about 6.1 deaths per day. Infants were the ones who most progressed to the intensive care unit (24.7%) and had the highest gross number of deaths (n = 2,012), but mortality was higher among adolescents (5.7%), reaching 9.8% in phase 1. The first peak of deaths occurred in phase 1 (May/2020), and two other peaks occurred in phase 4 (March/2021 and May/2021). There was an increase in cases and deaths for younger ages since phase 4. Hospital mortality in the pediatric population was higher in phases 1, 4, and 6, following the phenomena of dissemination/interiorization of the virus in the country, beginning of the second wave and beginning of the third wave, respectively. CONCLUSION The absolute number of cases of covid-19 in children and adolescents is significant. Although complete vaccination in descending order of age provided a natural deviation in age range, there was a greater gap between the curve of new hospitalized cases and the curve of deaths, indicating the positive impact of immunization.